Mechanochemical Formation of Racemic Praziquantel Hemihydrate with Improved Biopharmaceutical Properties - Debora Zanolla; Dritan Hasa; Mihails Arhangelskis; Gabriela Schneider-Rauber; Michele R. Chierotti; Jennifer Keiser; Dario Voinovich; William Jones; Beatrice Perissutti (MDPI AG, 2020)
Praziquantel (PZQ) is the first-line drug used against schistosomiasis, one of the most common parasitic diseases in the world. A series of crystalline structures including two new polymorphs of the pure drug and a series of cocrystals of PZQ have been discovered and deposited in the Cambridge Structural Database (CSD). This work adds to the list of multicomponent forms of PZQ a relevant example of a racemic hemihydrate (PZQ-HH), obtainable from commercial PZQ (polymorphic Form A) through mechanochemistry. Noteworthy, the formation of the new hemihydrate strongly depends on the initial polymorphic form of PZQ and on the experimental conditions used. The new PZQ-HH has been fully characterized by means of HPLC, Differential Scanning Calorimetry (DSC), Thermogravimetric Analysis (TGA), Hot-Stage Microscopy (SEM), Powder X-Ray Diffraction (PXRD), Scanning Electron Microscopy (SEM), FT-IR, polarimetry, solid-state NMR (SS-NMR), solubility and intrinsic dissolution rate (IDR), and in vitro tests on Schistosoma mansoni adults. The crystal structure was solved from the powder X-ray diffraction pattern and validated by periodic-DFT calculations. The new bioactive hemihydrate was physically stable for three months and showed peculiar biopharmaceutical features including enhanced solubility and a double intrinsic dissolution rate in water in comparison to the commercially available PZQ Form A.